(untitled) (Third Sector Social Economic Review, 2019)
The changing economic conditions force banks, which are important actors in the finance sector to use their resources effectively. The effective functioning of banks in the development of national economies is highly important both economically and socially. This sector, which is one of the basic institutions of financial markets, needs to be carefully monitored. The purpose of this study is to measure the effectiveness of bank deposits in Turkey with DEA method. For this purpose, the efficiency of 20 deposit banks operating under the period 2013-2018 was measured with assumptions of CCR and BCC by the input oriented DEA method. Consequently, 1 public, 3 private and 5 foreign capital banks were active. Foreign capital banks are more effective than public and private capital banks. Also, the reference banks for ineffective banks to be effective and the potential improvement ratios related to the input and output variables were determined.